Identification Skills Fish Diversity and Potential Use of Genome Data - Munandar, Rifki Risma; Hidayat, Topik; Sanjaya, Yayan (Jurnal Penelitian Pendidikan IPA, 2023)
Identification skills are essential for students to increase awareness of will importance of diversity and active protection. Grouping species based on information genome is well considered in effort conservation. Research objectives to describe courses diversity and classification vertebrates (KKV) in identifying fish morphology, genome, and perception student about identification diversity through genome data in one LPTK in Bogor. This research uses qualitative with 27 students in The Biology Education Study Program in one LPTK in Bogor in the odd semester 2022/2023. Data collection about results interviews, documentation, and responses implementation of the pre-college program. Analysis of research data done qualitatively. Research results describe that ongoing study. This does not yet give optimal knowledge in fish diversity in a manner morphology until genome. Findings this give description will need students to identify species in a manner morphology until genome and needed databases that can identify diversity in detail and available essential internal identification feature application.